An analysis of operational management in a multinational of industrialized mortars under the lean manufacturing principles - Barbosa, Miriam Ercelita (2019)
The main objective of this work is to analyze the operations management system of an industrial mortars company with multiple manufacturing units from the perspective of applying the Lean Manufacturing principles. It is intended to understand how these controls are deployed and show up if diagnosis based on the Lean management strategy is able to demonstrate opportunities for improvement in the management of production setup, total productive maintenance, pull production and continuous flow, supply chain integration, management visual, quality control, standardized operations, continuous improvement and labor flexibility. Thus, for this work, the methodology used was descriptive through the case study, using data collection and treatment applied to managers of the manufacturing units, documentary analysis, participative observation of the researcher and interviews with regional managers. The result of the survey highlighted the points with improvement opportunities.